Hubungan Antara Tingkat Adiksi Internet Dengan Derajat Depresi Pada Siswi di SMK 1 Batik Surakarta - Sari, Wahyu Dwi Tanjung, Dr. Erna Herawati, Sp.K.J (2017)
CORRELATION BETWEEN INTERNET ADDICTION LEVELS AND DEPRESSION LEVELS IN FEMALE STUDENTS OF SMK 1 BATIK SURAKARTA : (1)Over 70% of children and teenagers suffers from an undiagnosed and untreated depression. Internet addiction consists of every online activity such as social meda, email, pornography, online gambling, online games, chatting, etc. Several studies have suggested that internet addiction is correlated with overall decrease in quality of life and an increase in depression. (2) This study is an analytical observational study with a cross sectional approach and conducted at SMK 1 Batik Surakarta on November 2016. A total of 66 female students of SMK 1 Batik Surakarta were recruited as samples. Data were colleceted using IAT and CDI questionnaires, which were furtherly analyzed statistically with Product Moment / Pearson correlation test. (3)This study is an analytical observational study with a cross sectional approach and conducted at SMK 1 Batik Surakarta on November 2016. A total of 66 female students of SMK 1 Batik Surakarta were recruited as samples. Data were colleceted using IAT and CDI questionnaires, which were furtherly analyzed statistically with Product Moment / Pearson correlation test. (4) Pearson correlation test revealed a correlation value (r) of 0,345 , which shows a weak correlation between internet addiction and depresion levels in female students of SMK 1 Batik Surakarta. Further analysis revealed a p value = 0,005, p < 0,05 which shows that the correlation is statistically significant.(5) There is a correlation between internet addiction levels and depression levels in female students of SMK 1 Batik Surakarta.